Cover Image, Volume 94, Number 11, November 2022. Issue 11 (13th September 2022) - Yang, Yi; Zhao, Rongtao; Wang, Yule; Song, Dan; Jiang, Bo; Guo, Xudong; Liu, Wanying; Long, Feng; Song, Hongbin; Hao, Rongzhang
Abstract : Front Cover Caption : The cover image is based on the Research Article Rapid and universal detection of SARS‐CoV‐2 and influenza A virus using a reusable dual‐channel optic fiber immunosensor by Yi Yang et al., https://doi.org/10.1002/jmv.28015 .